2014
DOI: 10.1073/pnas.1323106111
|View full text |Cite
|
Sign up to set email alerts
|

RSPO–LGR4 functions via IQGAP1 to potentiate Wnt signaling

Abstract: R-spondins (RSPOs) and their receptor leucine-rich repeat-containing G-protein coupled receptor 4 (LGR4) play pleiotropic roles in normal and cancer development as well as the survival of adult stem cells through potentiation of Wnt signaling. Current evidence indicates that RSPO-LGR4 functions to elevate levels of Wnt receptors through direct inhibition of two membrane-bound E3 ligases (RNF43 and ZNRF3), which otherwise ubiquitinate Wnt receptors for degradation. Whether RSPO-LGR4 is coupled to intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 55 publications
3
108
0
1
Order By: Relevance
“…This complex results in the inhibition and membrane clearance of these E3 ubiquitin ligases, leading to increased Frizzled and LRP5/6 proteins on the cell surface (43,54). The LGR RSPO complex may also enhances b-catenin-dependent signaling by promoting MEK1/2-mediated phosphorylation of LRP5/6 and b-catenin-independent signaling through regulation of actin dynamics (55).…”
Section: R-spondin Translocations and Gene Amplificationmentioning
confidence: 99%
“…This complex results in the inhibition and membrane clearance of these E3 ubiquitin ligases, leading to increased Frizzled and LRP5/6 proteins on the cell surface (43,54). The LGR RSPO complex may also enhances b-catenin-dependent signaling by promoting MEK1/2-mediated phosphorylation of LRP5/6 and b-catenin-independent signaling through regulation of actin dynamics (55).…”
Section: R-spondin Translocations and Gene Amplificationmentioning
confidence: 99%
“…A number of previous studies have indicated that RSPOs may potentiate Wnt signaling via stimulation of the leucine-rich repeat-containing G-protein coupled receptors (LGR) 4, LGR5 and LGR6 (16)(17)(18). Wnt proteins, comprising a large family of extracellular, lipid-modified glycoproteins, are crucial for embryonic development and cell proliferation, regulation, differentiation, survival and tissue homeostasis in adults (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that canonical Wnt/β-catenin signaling serves an important role in numerous cancer types, including lung, breast, brain, colorectal and liver tumors (21)(22)(23). Interaction between RSPOs and LGR4, as well as the intracellular signaling proteins, promotes phosphorylation of LRP5/6, stabilizes β-catenin expression and promotes its transcriptional activity (18). Activation of Wnt/β-catenin results in the increased expression level of its target genes, including cyclin D1 and c-Myc, which are important for driving tumorigenesis in numerous types of cancer (24).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a reduction of RSPO3 expression, which is the consequence of the mosaic RSPO3 deletion in our proband's cells, 9 was already linked to the opposite of our findings, namely a reduction in cell proliferation and migration, in RSPO3 knockdown cancer cells. 47,48 The expression of NREP in BRCA1 mosMe was unaffected by the deletion 9 and no connection of this gene to cancerogenesis is known to date. It is beyond the scope of our present study, but remains to be determined, whether the deletions of RSPO3 and NREP co-exist with the BRCA1 epimutation in the same cells of the BRCA1 mosMe fibroblasts.…”
Section: Discussionmentioning
confidence: 99%